Fabrication of electron transparent 2D device for atomic scale electrical potential mapping in a TEM - Lim, Ming Han (Nanyang Technological University, 2022)
Two-dimensional (2D) materials have been studied immensely in the past decades especially since the discovery of a simple mechanical exfoliation method for graphene in 2004. Electronic device made using 2D materials offer exciting opportunities to miniaturise electronic products especially in the field of semiconductor. Transistor is one technology that could face a slowdown in development as Moore’s Law might be coming to an end soon. 2D field effect transistor (FET) based on 2D materials could potentially extend Moore’s Law and overcome many limitations of 3D FET such as short channel effect (SCE). However, while electronic device pushes for smaller size, the electrical characterization methods commonly used still only measure the bulk electrical properties instead of at smaller level. In this study, we developed a method to fabricate 2D devices to study the spatial electrical properties (e.g. electric field) of 2D materials at atomic level using transmission electron microscopy (TEM). The findings serve as important steps in overcoming the difficulties to fabricate an electron transparent 2D device which aims to allow more direct analysis of the local electric field of 2D materials in 2D devices.